Effectiveness of rikkosan gargling for burning mouth syndrome. Issue 2 (2nd May 2017) - Nakazawa, Seitaro; Okada, Kazutaka; Matsushita, Takae; Hegozaki, Seiji; Sakata, Ken‐ichiro; Kitagawa, Yoshimasa; Yamazaki, Yutaka
ABSTRACT: Case: Burning mouth syndrome (BMS) is characterized by a burning sensation or other dysesthesias of the oral mucosa, without accompanying abnormal clinical or laboratory findings. Although various treatment options have been proposed, there is currently no optimal approach. This report describes the cases of two women, aged 65 and 75 years, with BMS. The first patient had tongue pain, which disappeared after treatment with antidepressants, but which recurred 9 months later. The second patient had burning pain in the tongue and a continual phantom sensation of bitterness. Both patients were prescribed rikkosan as a mouthwash. Outcome: Initial gargling with rikkosan relieved the burning pain in both patients for approximately 60 min. Continuous treatment gradually reduced the frequency of symptoms, while also increasing the duration of symptom‐free periods. Symptoms disappeared after 4 and 10 months, respectively. Conclusion: Rikkosan gargling may be a useful adjuvant treatment for BMS.